FEATURES OF MOUNTED VENTILATED FACADE HEAT CONTROL SYSTEMS IN CONSTRUCTION PROJECTS - D. F. Karpov; M. V. Pavlov; A. A. Sinitsyn; N. N. Monarkin; A. G. Gudkov (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Abstract. Aim. An integral part of an energy audit of buildings and structures consists in thermal imaging diagnostics. This permits an evaluation of the heat-shielding properties of the enclosing structures of buildings in order to control the functional and operational status of engineering systems, as well as to identify implicit (invisible) and explicit (visible) defects in them. The aim of the work is to analyse some features and results of thermal control of an opaque hinged ventilated facade system and translucent enclosing structures in the form of window systems of a capital construction project. Method. Thermal imaging was used as a control for resolving issues of energy and resource conservation. The special importance of thermal control of translucent facade systems and non-translucent hinged ventilated facades of capital construction projects having various functional and operational purposes is highlighted. Results. A detailed algorithm is presented for supporting a comprehensive diagnosis of the heat engineering state of building envelopes for various construction projects by analysing thermograms, using thermal monitoring methods, to take into consideration engineering systems, building materials and finished products, along with technologies of full-scale thermal imaging inspection of translucent building envelopes. The obtained thermograms are presented and analysed. Conclusion. Current problems in the fields of energy efficiency and energy saving in the construction and energy industries are considered in the light of the latest technological developments. The proposed graph-analytical algorithm supporting a diagnosis of the heat engineering state of building envelopes based on the analysis of thermograms is the most comprehensive among known analogues and prototypes